IMPLEMENTASI DATA MINING PENGELOMPOKAN TINGKAT KEPUASAN PELANGGAN PADA PT. BISA GROUP MENGGUNAKAN FUZZY C-MEANS - Maria Yostin Br Tarigan; Mita Aprila Silpa Simanjuntak; Musa Andrew Loyd Sitanggang; Etriska Prananta S.; Delima Sitanggang (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Bisa Group is a company engaged in the Food & Beverage sector. The company records a large number of sales transactions every day, which results in a rapid accumulation of customer data in the database. When the amount of customer data is still small, manual analysis and interpretation methods with human skills are still possible. However, with rapid growth, it is important to monitor customer satisfaction levels to prioritize restaurants that have low satisfaction levels for immediate improvement. The purpose of this monitoring is to increase the number of customer transactions and reduce the possibility of customers switching to other restaurants. By using the Fuzzy C-Means method, customer data can be grouped and focused on customer satisfaction. The results showed that consumer perceptions of service quality were 84% very satisfied, 16% of consumer assessments of service were not satisfied. In clustering analysis using the Fuzzy C-means method, it is concluded that the majority of respondents in the dataset show a very high level of satisfaction with Restaurant services. The benefit of this research is to provide recommendations in improving service quality and become a reference for the company.